P4_1 Somewhere over the rainbows! - Sainty, William; Graham, Holly; Kneeshaw, Sam; Howard-Clark, Simon (Physics Special Topics, 2017)
In this paper, we have discussed what a rainbow produced by dispersion through water droplets looks like from the surface of a planet orbiting a binary star system. The physics of rainbows was examined and a radius of curvature was found to be 42o. How rainbows would appear in a real circumbinary star system, Kepler-34, was studied and we found that two rainbows, 12o apart and 84o across, would be visible on the planet’s surface.